2010
DOI: 10.4103/0970-1591.65408
|View full text |Cite
|
Sign up to set email alerts
|

Lymphangioma circumscriptum of the scrotum following vasectomy

Abstract: Lymphangioma circumscriptum is a congenital lymphatic hamartoma and rarely occurs in the male genital organs. Here we report a case of acquired lymphangioma circumscriptum of scrotum following vasectomy, which has not been reported till date. High clinical suspicion index is the clue to the clinician for diagnosis; histopathological confirmation and adequate surgical excision with deep lymphatic cisterns give the best result.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
22
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 2 publications
(1 reference statement)
1
22
0
1
Order By: Relevance
“…The condition, especially in the genital region, is difficult to diagnose. Pal et al reported a case of AL circumscriptum of the scrotum within two weeks after the vasectomy operation [3]. Similarly, the lesions in our patient occurred on the glans as asymptomatic grouped vesicles within 2 weeks after circumcision.…”
Section: Clinical Lettersupporting
confidence: 72%
“…The condition, especially in the genital region, is difficult to diagnose. Pal et al reported a case of AL circumscriptum of the scrotum within two weeks after the vasectomy operation [3]. Similarly, the lesions in our patient occurred on the glans as asymptomatic grouped vesicles within 2 weeks after circumcision.…”
Section: Clinical Lettersupporting
confidence: 72%
“…Acquired LC develops in advanced age, possibly due to injury to deep collecting lymphatics, caused by trauma, surgery, radiotherapy or infections such as filariasis, lymphogranuloma venereum, donovanosis or tuberculosis [5]. LC is clinically identified by translucent or hazy vesicles of different sizes which are grouped like frog spawn or, less commonly, as diffuse swelling to a particular area.…”
Section: Discussionmentioning
confidence: 99%
“…LC is clinically identified by translucent or hazy vesicles of different sizes which are grouped like frog spawn or, less commonly, as diffuse swelling to a particular area. These swellings frequently have accompanying verrucous alterations giving them a warty appearance and, if there is significant hyperkeratosis, the swelling may clinically resemble lymphogranuloma venereum [5]. A strong clinical suspicion is needed for diagnosis of this disease with histopathological confirmation.…”
Section: Discussionmentioning
confidence: 99%
“…Various treatment modalities are available such as radiofrequency ablation, sclerotherapy, ablative lasers, and surgical excision of both the superficial as well as deep components to prevent recurrence of lesion which is the most common postoperative complication with recurrence rate up to 25–50% in the 1 st 3 months. [ 1 3 ]…”
mentioning
confidence: 99%